THE YOUNG GENERATION INTEREST IN STUDYING TRADITIONAL MUSICAL INSTRUMENTS AS A FORM OF CULTURAL LOVE AT BUNDA MULIA UNIVERSITY SERPONG - Roozana Maria Ritonga BBA; Veronica Veronica (Jurnal Cakrawala Ilmiah, 2022)
Traditional music is a hereditary heritage that we should support considering that Indonesia has a variety of cultures and arts that differ from region to another. One way to preserve the culture of the younger generation is to learn traditional musical instruments in general, such as gamelan, kolintang, angklung, sasando and others with the hope that these traditional musical instruments can still be used during cultural and artistic events or just for entertainment. But, with the development of technology today, many of these young generation do not even care and they do not even have a musical taste to learn this musical instrument, they even more interested in learning western music with its more interesting and modern presentation unlike traditional music which they think is outdated. This research was made with the aim first, what factors influence the interest of the younger generation or students in this era of globalization in studying traditional musical instruments at Bunda Mulia University Serpong, second, how much interest students have in learning traditional musical instruments, and three what obstacles faced by students in playing traditional musical instruments and finally to find out which traditional musical instruments are in great demand by students at the University of Bunda Mulia Serpong. The theory used in this study is the theory of interest and learning, while the research method used is a qualitative approach with data conducted through primary surveys, namely interviews and observations with Bunda Mulia University students from the hospitality and tourism study program by providing structured questions and interviews at students which were done online. As for secondary surveys such as library and journal studies to find supporting data related to the research theme. The results of the study provide an answer that the factors that underlie students' interest in learning traditional musical instruments is curiosity or eager to know of something, also student are interested in learning traditional musical instruments because they have studied these musical instruments before, as for the obstacles faced by students in learning traditional musical instruments were influenced among others, by not having the talents or interests of students as well as incomplete musical instruments and lack of qualified teachers, however the traditional musical instruments that interest to students is the traditional instrument of Angklung because they are familiar to its strains and melodies as well as unique musical instruments because they are played by swinging them. Thus, it can be concluded that the younger generation of Bunda Mulia University Serpong is interested in learning traditional musical instruments.